DOUBLE BLIND RANDOMIZED CONTROLLED STUDY ON THE EFFICACY OF ASPARAGUS RACEMOSUS MOTHER TINCTURE IN HYPERLIPIDEMIA - Geeta B Adi, Geeta B Adi; Basavaraj S Ad, Basavaraj S Ad; Siva Rami Reddy E, Siva Rami Reddy E (International Journal of Indigenous Herbs and Drugs, 2018)
Aim: Asparagus racemosus has anti toxidant, anti inflammatory and anti diabetic activities. In the present double blind randomized controlled study is that efficacy of asparagus racemosus mother tincture in hyperlipidemia. Hyperlipidemia patients meeting the inclusion criteria were randomly assigned in to the treatment and placebo. Methods: 50 patients in treatment group took asparagus racemosus mother tincture; whereas the patients in placebo group took placebo mother tincture for 12 weeks. The lipid profiles of the patients were evaluated at baseline, and after 6 and 12 weeks of the double blind randomized controlled study. Results: The final results showed that asparagus racemosus mother tincture significantly p value 0.05 improved LDL, HDL, cholesterol, compared to the placebo group. The asparagus racemosus showed an inhibitory effect on of hepatic enzymes and possible liver toxicity. No serious side effect was reported for asparagus racemosus mother tincture administration. Therefore, asparagus racemosus mother tincture could be considered as a supplement for treatment of dyslipidemia.